Transcriptional Regulation of Fibroblast Growth Factor-2 Expression in Human Astrocytes: Implications for Cell Plasticity - Moffett, John (The American Society for Cell Biology, 1998)
Induction of the fibroblast growth factor-2 (FGF-2) gene and the consequent accumulation of FGF-2 in the nucleus are operative events in mitotic activation and hypertrophy of human astrocytes. In the brain, these events are associated with cellular degeneration and may reflect release of the FGF-2 gene from cell contact inhibition. We used cultures of human astrocytes to examine whether expression of FGF-2 is also controlled by soluble growth factors. Treatment of subconfluent astrocytes with interleukin-1β, epidermal or platelet-derived growth factors, 18-kDa FGF-2, or serum or direct stimulation of protein kinase C (PKC) with phorbol 12-myristate 13-acetate or adenylate cyclase with forskolin increased the levels of 18-, 22-, and 24-kDa FGF-2 isoforms and FGF-2 mRNA. Transfection of FGF-2 promoter–luciferase constructs identified a unique −555/−513 bp growth factor-responsive element (GFRE) that confers high basal promoter activity and activation by growth factors to a downstream promoter region. It also identified a separate region (−624/−556 bp) essential for PKC and cAMP stimulation. DNA–protein binding assays indicated that novel cis-acting elements and trans-acting factors mediate activation of the FGF-2 gene. Southwestern analysis identified 40-, 50-, 60-, and 100-kDa GFRE-binding proteins and 165-, 112-, and 90-kDa proteins that interacted with the PKC/cAMP-responsive region. The GFRE and the element essential for PKC and cAMP stimulation overlap with the region that mediates cell contact inhibition of the FGF-2 promoter. The results show a two-stage regulation of the FGF-2 gene: 1) an initial induction by reduced cell contact, and 2) further activation by growth factors or the PKC-signaling pathway. The hierarchic regulation of the FGF-2 gene promoter by cell density and growth factors or PKC reflects a two-stage activation of protein binding to the GFRE and to the PKC/cAMP-responsive region, respectively.